Nilai Pendidikan Karakter pada Film Big Brother dan Impelementasinya terhadap Pembelajaran Bahasa Indonesia - Rasmi, Rasmi; Idawati, Idawati; Azis, Abdul (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the character education values contained in the film Big Brother and the implementation of character education values for Indonesian language learning of grade XI students. This type of research is qualitative research. The data collected in this study are statements in the form of words, clauses, sentences that contain character education values in the film. The research data source is a film entitled Big Brother with a duration of 1 hour 41 minutes. Data collection techniques were carried out through observation, interviews, and direct observation. The data analysis that will be used by researchers in this study is content analysis, which is research conducted on information documented in recordings, whether in the form of images, sound, or writing. The results of the study revealed that the form of character education values found in the film Big Brother, including the value of honest character education, discipline, hard work, creativity, independence, love for the country, friendly/communicative, peace-loving, fond of reading, social care, and responsibility. The film did not find the character education values of religious, tolerance, democracy, curiosity, national spirit, respect for achievement, and environmental care. The character education values found in the film Big Brother and relevant to the core competencies in Indonesian language learning at SMA Negeri 19 Bone include honesty, discipline, creativity, independence, social care, and responsibility.